Analisis Komparatif Sistem Keuangan Publik Dunia Kuno, Eropa Abad Pertengahan, dan Islam Awal dalam Perspektif Keadilan Sosial - Raihan Muzaki; Deri Putra Liwando; Nana Apriana; Raisya Ratutiantri Pakusudewa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study describes a comparative analysis of public financial systems in the ancient world, medieval Europe, and early Islam from a social justice perspective. The purpose of this study is to analyze the public financial systems of the ancient world, medieval Europe, and early Islam from a social justice perspective. The research method is qualitative. Data analysis was conducted using thematic analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The results of this study indicate that the ancient world had an administratively efficient financial system but was highly centered on the power of the ruler, resulting in high social inequality. In medieval Europe, the financial system was influenced by feudalism and religious values, but was fragmented and dependent on the elite, resulting in an unequal distribution of wealth. Meanwhile, early Islam presented a more structured financial system through the Baitul Mal (Financial Treasury) and instruments such as zakat, kharaj, and jizyah, oriented towards social justice and wealth redistribution. However, all three systems have their respective weaknesses, especially in aspects of implementation, accountability, and equity. This study concludes that social justice in the public financial system requires the integration of institutional efficiency, ethical values, and strong redistribution mechanisms.